A Direct Synthesis of Highly Substituted π‐Rich Aromatic Heterocycles from Oxetanes. Issue 35 (21st July 2017) - White, Alexander R.; Kozlowski, Ryan A.; Tsai, Shiou‐Chuan; Vanderwal, Christopher D.
Abstract: The ubiquitous use of π‐rich five‐membered heterocycles has driven the development of new methods for their synthesis for more than a century. Here, we disclose a general and reliable reaction manifold for the construction of highly substituted heterocycles through a facile Lewis‐acid‐catalyzed oxetane rearrangement. Notably, this methodology employs a keto‐oxetane motif as a 1, 4‐dicarbonyl surrogate, which can be synthesized using robust alkylation or alkenylation reactions, and thus obviates the need to access 1, 4‐dicarbonyl compounds via umpoled starting materials. We harnessed this reactivity to generate a broad range of substituted furans and pyrroles, and extended this methodology to produce benzo‐fused versions thereof. Abstract : Upon alkenylation or addition to the keto function of inexpensive 3‐oxetanone, the strained oxetane ring is poised for a facile and general rearrangement to make important heterocycles.